Intrinsic and extrinsic effects on behavioral tax biases in risky investment decisions - Martin Fochmann; Kristina Hemmerich; Dirk Kiesewetter (Arbeitskreis Quantitative Steuerlehre (arqus), 2015)
In a variety of recent papers, it is shown that individuals do not take taxes correctly into account, which results in distorted or unexpected investment behavior. We shed further light on the discussion of such behavioral tax perception biases by analyzing intrinsic and extrinsic effects on decision behavior. We study two dimensions: (1) the influence of emotions and cognition (individual dimension, intrinsic effects) and (2) the influence of available tax information by varying tax complexity and salience (tax system dimension, extrinsic effects). In our laboratory experiment, we construct the payoff structure such that the subjects are confronted with exactly the same choices in net terms in a situation with or without a capital gains tax. This design allows us to identify pure tax perception biases. We show that both dimensions are able to explain tax perception biases. In particular, we find evidence that perceived risk (cognition) is lower and consequently willingness to take risk is higher with a capital gains tax (with full loss offset provision) than without taxation. Furthermore, this positive effect on risky investment is higher in a situation with a rather low level of tax information in which tax complexity is high and tax salience is low. In addition, we are able to provide evidence that the use of decision heuristics can explain the observed tax bias differences between our information treatments. In particular, we find a negative relationship between the information level and the use of heuristics.
Keywords: C91; D14; H24; 330; Tax Perception; Behavioral Taxation; Risk Taking Behavior; Tax Complexity; Tax Salience; Affect and Cognition; Experimental Economics